Diversity of Marine Snakes on Trawling Grounds in the Straits of Malacca and the South China Sea - VORIS, HAROLD K. (Tropical Natural History, 2017)
Prior to World War II, traditional hand-operated fishing methods prevailed throughout Southeast Asia. However, by 1950, mechanized diesel-powered trawlers were being introduced and the modern boom-and-bust of fisheries was set into motion. Besides targeted fish, squid, and prawns, otter trawls on the bottom brought up a vast diversity of demersal by-catch including marine snakes. This paper reports on the diversity of the marine snake by-catch obtained from otter trawlers operating at two locations in the Straits of Malacca (Sungai Buloh and Parit Botak) and one location on the eastern coast of the Malay Peninsula (Endau) in the mid-1970s. At Sungai Buloh 11 species of snakes were observed and a single species, Hydrophis curtus, strongly dominated the assemblage, comprising 82% of the by-catch. Eleven species were also observed in the by-catch from Parit Botak but there, three species (Hydrophis fasciatus, H. curtus, and Aipysurus eydouxii) shared dominance with each making up more than 22% of the assemblage. At Endau, 13 species appeared in the by-catch and two species (H. curtus and Hydrophis viperinus) dominated, comprising 33% and 32% of the catch respectively. Besides differences between locations, some small differences in species diversity were detected between collection periods at Sungai Buloh. In addition, a review is undertaken of published trawl surveys of marine snakes in Southeast Asia in the context of the steady depletion of fisheries in the region that took place in the second half of the twentieth century. This review emphasizes that marine snake species diversity needs to be understood on a relatively fine spatial scale and in the context of the health of the fishery as a whole.